Stabilizing nanocrystalline Cu2O with ZnO/rGO: Engineered photoelectrodes enables efficient water splitting. Issue 6 (15th March 2021) - Shanmugasundaram, Arunkumar; Johar, Muhammad Ali; Boppella, Ramireddy; Kim, Dong-Su; Jeong, Yun-Jin; Kim, Jong Yun; Hassan, Mostafa Afifi; Ryu, Sang-Wan; Lee, Dong Weon
Abstract: The engineered photoelectrodes have received significant attention in the photoelectrochemical (PEC) applications. Herein, we prepared a highly effective photoelectrode based on Cu2 O decorated with ZnO and rGO for efficient PEC water splitting. Firstly, different thickness Cu2 O is sputtered on the FTO substrate (FC). The PEC performance of the FC photoelectrode further improved by depositing the ZnO and rGO protection layers (FCZG). The fabricated photoelectrodes are systematically investigated for their morphological and crystal structure by AFM, FESEM, TEM, XPS, XRD, and RAMAN, UVDRS, and PL analysis. The FCZG hybrid photoelectrode exhibit a photocurrent density of 4.94 mA cm −2 at 0 V vs . reversible hydrogen electrode (RHE), which is 1.5 times higher than the unmodified photoelectrodes. The improved PEC performance of the FCZG hybrid photoelectrode is due to the high surface roughness, larger electrochemical active surface area, and less radiative recombination rate of the photogenerated charge carriers.